Description of Obesity Characteristics in Elderly with Walking Disturbance - Anggraeni, Rina; Luthfiana, Lulu; Jati, Riani Pradara; Aeni, Qurrotul; Nurwijayanti, Andriyani Mustika (Global Health Science Group, 2024)
A person who has reached the age of 60 years and over will experience an aging process which is characterized by changes such as decreased memory, muscles that are no longer flexible, decreased hearing and vision function, and problems walking. Barriers to walking can cause limitations in moving independently using the feet in an environment to be disrupted because it can slow down something a person is doing. Barriers to walking in the elderly are characterized by several characteristics, including obesity. This study aims to determine the characteristics of obesity in elderly people with walking obstacles in Kendal Indonesia. The design of this research is descriptive qualitative. The research population was 45 elderly people using a total sampling technique. Data were collected using the Body Mass Index (BMI) calculations as an International standard. Body mass index (BMI) is the method of utilizing an adult's height and weight to broadly place them into underweight, normal weight, overweight and obese categories. BMI can be calculated using metric or imperial (US) units.The results of this study showed that thin body weight (6.7%), normal body weight (68.9%), fat body weight (13.3%), and obese body weight (11.1%). Obesity causes obstacles to walking.